2022
DOI: 10.3390/ijerph19116663
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Mothers of High Functioning Autism Spectrum Disorder (HFASD)Adolescents

Abstract: Autism Spectrum Disorder (ASD) has become more prevalent globally. The disorder is predominantly characterised by low social skills noted explicitly in people with High Functioning Autism Spectrum Disorder (HFASD). The individuals usually possess a normal or superior intelligence quotient (IQ) but the disability impedes the achievement of their actual high potential, hence compromising their quality of life (QoL). Managing adversities encountered by children with HFASD often compromises the QoL of the entire f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Studies showed that parents can implement therapeutic strategies well and at an acceptable level by receiving special training. Because PMI relies on parents spending significant time with children, it can have a significant impact on the active participation of parents and children in the treatment process [7][8][9][10]. Also, these methods are cost-beneficial in terms of time and cost.…”
Section: Family-centered Interventions Are Recognized As Parentmediat...mentioning
confidence: 99%
“…Studies showed that parents can implement therapeutic strategies well and at an acceptable level by receiving special training. Because PMI relies on parents spending significant time with children, it can have a significant impact on the active participation of parents and children in the treatment process [7][8][9][10]. Also, these methods are cost-beneficial in terms of time and cost.…”
Section: Family-centered Interventions Are Recognized As Parentmediat...mentioning
confidence: 99%
“…Specific interventions to support mothers of children with ASD have been identified as important (Nahar et al, 2022). A study exploring the QOL of mothers of adolescents with high-functioning ASD identified certain domains that could improve resilience (Mohamad Aun et al, 2022). By considering mothers' QOL, clinicians and researchers can gain a better understanding of their challenges and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Nurturing an adolescent into a young adult is particularly stressful for many parents, as they encounter challenges such as accessing services; difficulties in adapting to transition changes and managing multiple responsibilities; and vocation and higher education challenges (Aun et al, 2022;First et al, 2016). Most parents are concerned about their child's level of independence and how they will cope when they can no longer care for them (Yaacob et al, 2021).…”
Section: Introductionmentioning
confidence: 99%